Evaluation of progenies of half-sibs of the corn population CMS-453 - Carvalho, Hélio Wilson Lemos de; Guimarães, Paulo Evaristo de Oliveira; Leal, Maria de Lourdes da Silva; Carvalho, Paulo César Lemos de; Santos, Manoel Xavier dos (Pesquisa Agropecuaria Brasileira, 2000)
Three cycles of selection among and within the progenies of half-sibs were realized in the corn population CMS-453, for high protein quality, in the period of 1995 to 1997, in the Northeastern Brazil, with the objective of obtaining more productive germplasm, well adapted, with good agronomic characters, high percentage of tryptophan and lysine the protein to be utilized in the region. The 196 progenies, in each cycle, were evaluated in a 14 x 14 lattice, with two repetitions, doing the combination of the selected progenies in the same agricultural year, in the way of obtaining a cycle each year. The magnitude of the estimated genetic parameters decreased from the original cycle to the selection cycle I, increasing from cycle I to cycle II. The high values of these magnitudes associated with the high productivity means of the progenies and with the expected and obtained averaged gain from the selection among and within progenies per selection cycle of 11.62% and 3.0%, respectively, show the high potential of the population to respond to selection which will permit to attain a higher production and a material better adapted to the regional environment. The percentages of tryptophan and lysine in the protein, in average of the three cycles of selection were 0.88% and 3.91% giving a high genetic quality for the CMS-453 population.
Keywords: Zea mays; selection; breeding methods; genetic gain